2015
DOI: 10.3402/qhw.v10.27990
|View full text |Cite
|
Sign up to set email alerts
|

Facing the fear of failure: An explorative qualitative study of client experiences in a mindfulness-based stress reduction program for university students with academic evaluation anxiety

Abstract: The aim of this qualitative study was to investigate the subjective experiences of 29 university students who participated in an 8-week mindfulness-based stress reduction (MBSR) program for academic evaluation anxiety. Participants who self-referred to the Student Counseling Service underwent individual semi-structured interviews about how they experienced the personal relevance and practical usefulness of taking the MBSR program. Interviews were transcribed and analyzed through a team-based explorative–reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 50 publications
(63 reference statements)
4
49
0
9
Order By: Relevance
“…These factors create increasing stress among students, both on-and offline (Robotham and Julian, 2006). University student cohorts have been found to have concerning rates of mental health issues (Andrews and Wilding, 2004;Bayram and Bilgel, 2008;Hjeltnes et al, 2015), and online student cohorts, particularly those adjusting to intensive study modes, face comparable challenges. In response, several efforts have been made by universities to support students and promote positive mental health and wellbeing in an attempt to combat increasing psychological distress (Regehr et al, 2013).…”
Section: Online Environment: Student Support and Well-being Servicesmentioning
confidence: 99%
“…These factors create increasing stress among students, both on-and offline (Robotham and Julian, 2006). University student cohorts have been found to have concerning rates of mental health issues (Andrews and Wilding, 2004;Bayram and Bilgel, 2008;Hjeltnes et al, 2015), and online student cohorts, particularly those adjusting to intensive study modes, face comparable challenges. In response, several efforts have been made by universities to support students and promote positive mental health and wellbeing in an attempt to combat increasing psychological distress (Regehr et al, 2013).…”
Section: Online Environment: Student Support and Well-being Servicesmentioning
confidence: 99%
“…Moreover, certain personality traits such as perfectionism and shyness may be correlated with psychopathologies observed within the student population. 1,2,[8][9][10][11][12][13][14] Although proper sleep hygiene has proved to be important for mental health, complaints of sleep problems are extremely common among university students. Research has linked these issues to depression and anxiety in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…This finding aligns with many studies reporting the positive effects of contemplative practices on student learning (Arnold, 2011;Franco et al, 2010;Ramsburg & Youmans, 2014;Schlesiger, 1995) but contrasts with results of a prior study (Yamada & Victor, 2012) that found no improvements in student grades. Previous research (e.g., Hjeltnes et al, 2015;Jha et al, 2007;Zeidan et al, 2010) has shown that contemplative practices enhance focus, attention, concentration, and processing, resulting in improved learning and performance. In the interview data, many students reported experiencing decreased levels of stress and worry and an increased ability to focus on learning and testing after having participated in the contemplative practices.…”
Section: Discussionmentioning
confidence: 95%
“…In a research review on universal promotion and prevention programs for higher education students, Conley, Durlak, and Dickson (2013) found that mindfulness-based interventions were the most effective in reducing students' levels of emotional distress (including depression, anxiety, and stress), as compared to cognitive-behavioral interventions, and those delivered in class (as opposed to in small group workshops/programs) were the most effective. In a qualitative study, college-level students with diagnosed anxiety who had participated in an MBSR program reported a greater sense of inner calm, a greater ability for focus and concentration in learning situations like studying or test-taking, approaching learning in more effective ways, and relating to their anxiety in new ways (Hjeltnes, Binder, Moltu, & Dundas, 2015).…”
Section: Benefits For Health and Well-beingmentioning
confidence: 99%